PENGEMBANGAN MEDIA PEMBELAJARAN IPA DENGAN ANIMAKER TEMA EKOSISTEM SAWAH DAN KOLAM DI KELAS 5 SEKOLAH DASAR - Sarah Fauziah; Sofi Mutiara Insani; Lutfi Nur; Elan; Seni Apriliya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the inability of students to think critically due to the use of learning media that is still simple. The solution to this problem is to develop learning media that is more interesting and easy to understand. The use of Animaker learning media aims to improve students' critical thinking and communication skills. The media to be used is Animaker software, an animation video creation platform designed to develop learning materials that are more interesting and easily understood by students. In addition, Animaker can be an alternative for educators in delivering material and facilitating the learning process. The learning media designed raised the theme of Rice Field and Pond Ecosystems for science subjects in grade 5 SDN 2 Sukamenak. The research method used is Educational Design Research (EDR), or educational design research that involves a cycle of analysis, design, development, evaluation, and revision. The results showed that the use of Animaker media helped students to develop themselves, become more active and creative, and more focused in understanding learning materials, so that learning became more effective and fun.